Factors associated with augmentation in patients with restless legs syndrome. (29th December 2021) - Heim, Beatrice; Ellmerer, Philipp; Stefani, Ambra; Bergmann, Melanie; Brandauer, Elisabeth; Seppi, Klaus; Högl, Birgit; Djamshidian, Atbin
Abstract: Background and purpose: Augmentation is a paradoxical reaction mainly to dopaminergic medication in patients with restless legs syndrome (RLS), but the exact pathomechanism remains unclear. The aim of this study was to identify factors associated with augmentation in RLS patients. Methods: RLS patients with and without current or previous augmentation were recruited. Demographic characteristics, history of smoking, questionnaires for depression, alexithymia, and impulsivity, and RLS severity were obtained. Results: We included 122 patients, of whom half had a history of augmentation. Patients with augmentation had a longer disease duration ( p = 0.001), had higher RLS severity scores ( p = 0.013), had higher levodopa equivalent doses ( p < 0.001), had higher scores for alexithymia ( p = 0.028), had higher prevalence of impulse control disorders ( p < 0.001), more often had a history of smoking ( p = 0.039), were more often currently smoking ( p = 0.015), and had more average pack‐years ( p = 0.016). Conclusions: Here, we describe several factors commonly associated with augmentation in RLS. These may help clinicians to screen and treat patients carefully to avoid the challenging side effect of augmentation. Abstract : Augmentation (AUG) is a paradoxical reaction mainly to dopaminergic medication in patients with restless legs syndrome (RLS), but the exact pathomechanism remains unclear. Here, we describe several factors commonly associated with augmentation in RLS. Patients with augmentation had a longer disease duration ( p = 0.001), higher RLS severity scores ( p = 0.013), higher levodopa equivalent doses (LED) ( p < 0.001), higher scores for alexithymia ( p = 0.028), a higher prevalence of impulse control disorders (ICDs) ( p < 0.001), had more often a history of smoking ( p = 0.039), were more often currently smoking ( p = 0.015), and had more average pack‐years ( p = 0.016).